2010
DOI: 10.1159/000318023
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y and Blood Donation: The Impact of Altruistic Help in a Darwiportunistic Scenario

Abstract: This article focuses on the members of Generation Y and their willingness to offer voluntary (unpaid) blood donations. Using statistics from various sources, a threestage model is developed to explain blood donation behaviour especially of this generation. It consists of i) developing altruism, ii) raising the willingness to donate blood, and iii) activating actual blood donation behaviour. Members of Generation Y live in a Darwinistic society. They also to some degree act opportunistically, but not in contrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Consistent with multiple reports of motivations in human blood donors, pro‐social motives were most frequently observed in this study 9 14 28–30 . This study suggested most motives were altruistic (helping others or saving lives) or empathic (towards other owners and sick animals).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with multiple reports of motivations in human blood donors, pro‐social motives were most frequently observed in this study 9 14 28–30 . This study suggested most motives were altruistic (helping others or saving lives) or empathic (towards other owners and sick animals).…”
Section: Discussionsupporting
confidence: 90%
“…Understanding the motivations of human blood donors is considered fundamental to improving the effectiveness of donor recruitment and retention programmes 8–10 . The most common motivating factors for human blood donors are convenience, prosocial and personal values, altruism, reciprocity and kinship 11–14 . Sociodemographic factors have also been shown to affect willingness and motivations to donate in human blood donors.…”
Section: Introductionmentioning
confidence: 99%
“…Altruism has been shown to have a positive correlation between attitudes toward blood donation and willingness to donate, for example, Evans and Scholz (69,70), which also shows that altruism plays an important role as a moral factor in the process of blood donation. China has a profound culture of benevolence, love and morality, and the concepts of collectivism and self-giving are more prevalent.…”
Section: The Influence On Altruism and Attitudes Toward Blood Donatio...mentioning
confidence: 97%
“…The bulk of donors have shifted due to health issues, travel deferral and ageing-out for the historically large baby boomer donor population. The broad behaviour change of today's donors likely follows generational trends, most notedly Generation Y and Millennials [17][18][19]. The long-term outcome of affecting donor behaviour using standard methods is sparse for these two populations [10,15].…”
Section: Introductionmentioning
confidence: 99%